A new image encryption algorithm with nonlinear-diffusion based on Multiple coupled map lattices. (July 2019) - Wang, Xingyuan; Zhao, Hongyu; Wang, Mingxu
Highlights: Multiple coupled map lattices (MCML) was proposed. The method of nonlinear-diffusion was proposed. The strategy of simultaneously shuffling and diffusion was adopted. The proposed scheme only needs one round of encryption to get good effects. The superior performance of the proposed algorithm was proved by experiments. Abstract: This paper proposes a new spatiotemporal chaos system named Multiple coupled map lattices (MCML). The proposed spatiotemporal chaos system has outstanding cryptographic features, which is very suitable for encryption algorithms. Based on this system, this paper proposes a new image encryption algorithm. The proposed algorithm employs the strategy of nonlinear-diffusion for the first time, and simultaneously performs shuffling and diffusion. The ciphertext value of each pixel in the diffusion phase depends on a chaotic interference value, a pixel value of the plain image, and two values of the ciphered image non-adjacent to it. This strategy reduces the correlation between adjacent pixels of the plain image as well as the correlation between the R, G and B components of color image. Theoretical analysis and experimental results prove the high efficiency and security of the proposed algorithm.